$\displaystyle y=(-x)^8-3(-x)^4+2(-x)^2+2$

lets look at the first term...

this is the same as $\displaystyle (-x)(-x)(-x)(-x)(-x)(-x)(-x)(-x)=x^8$

but if you wrote it as $\displaystyle -x^8$ it is the same as...

$\displaystyle (-1)\cdot(x)^8=(-1)(x)^8=-x^8$

different answers.

now lets look at the second term...

this is the same as

$\displaystyle (-3)\cdot[(-x)(-x)(-x)(-x)] = (-3)\cdot(x)^4=-3x^4$

but i though you could do this...

$\displaystyle (-3)\cdot(-x)^4=3x^4$

these are different answers.

which is correct?

i really hope this isn't another missing dollar riddle type situation because then i would feel silly.